2019
DOI: 10.1007/s11255-019-02296-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of spiral ileal neobladder with orthotopic ureteral reimplantation

Abstract: Purpose The purpose of this study was to analyze long-term complications, urodynamics, and quality of life (QoL) of patients after orthotopic ileal neobladder with orthotopic ureteral reimplantation to enrich clinical data and provide a basis for clinical use of this surgery. Methods Between January 2007 and January 2013, 72 consecutive patients who underwent spiral ileal neobladder following radical cystectomy were enrolled. The neobladder was created using a modified Camey-II technique. Complications were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…The vast majority of articles included in our SR were retrospective, with only a few (28.8%) prospective trials [8,12,13,15,[21][22][23]25,33,46,48,49,53,60,[63][64][65]. Only 13 (22%) report institutional review board approval [8,[13][14][15][20][21][22]25,33,40,53,64,65].…”
Section: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of articles included in our SR were retrospective, with only a few (28.8%) prospective trials [8,12,13,15,[21][22][23]25,33,46,48,49,53,60,[63][64][65]. Only 13 (22%) report institutional review board approval [8,[13][14][15][20][21][22]25,33,40,53,64,65].…”
Section: General Aspectsmentioning
confidence: 99%
“…Twenty (33.9%) studies [8,10,14,15,17,23,26,27,32,40,42,44,45,50,51,53,57,61,64,65] reported mean overall operating times. Only 6 studies (10.2%) [23,26,50,51,57,64] specified OT for the reconstructive part of the surgery.…”
Section: Surgical and Technical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A radical cystectomy (RC) is an effective method for the treatment of invasive bladder cancer, with an ileal orthotopic neobladder (ONB) reconstruction being an ileal method of urinary diversion [ 1 , 2 ]. An orthotopic neobladder should enable normal bladder function, keep adequate capacity at low pressure, create a continence mechanism, and prevent upper urinary tract dilatation via an antireflux mechanism [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radical cystectomy (RC) is an effective method for the treatment of invasive bladder cancer while ileal orthotopic neobladder (IONB) reconstruction is an ideal method of urinary diversion. 1 , 2 Due to the narrow and deep operation space behind retropubic, it is difficult to hold, insert, and withdraw the needle 3 If the neobladder-urethral anastomosis has some tension, the anastomosis will be more tedious. Therefore, neobladder-urethral anastomosis is considered as an important and critical step in these procedures.…”
Section: Introductionmentioning
confidence: 99%